2005
DOI: 10.1122/1.2039827
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic coalescence of thermotropic liquid crystalline polymers: The role of transient rheology

Abstract: SynopsisThe coalescence in air of two polymeric drops into a single drop ͑also referred to as sintering͒ was investigated for two thermotropic liquid crystalline polymers. Initial coalescence via elastic contact was ruled out based on the magnitude of the equilibrium compliance values and the process was, therefore, believed to be driven by surface tension and resisted by means of viscous flow.Remarkably the viscous coalescence model developed for Newtonian fluids ͑an extension of the Frenkel and Eshelby appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recent papers on ternary systems have suggested that composite droplet formation may be related to the viscosity of the dispersed components . Nemirovski et al studied the phase morphology of a number of three-component (thermoplastic/thermotropic) systems and suggested that the dispersed component A would encapsulate the dispersed component B (in a matrix C) when both the thermodynamics, expressed by means of a positive λ A/B spreading coefficient, and the kinetic effects, expressed by means of a dispersed phase viscosity ratio smaller than 1, acted cooperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers on ternary systems have suggested that composite droplet formation may be related to the viscosity of the dispersed components . Nemirovski et al studied the phase morphology of a number of three-component (thermoplastic/thermotropic) systems and suggested that the dispersed component A would encapsulate the dispersed component B (in a matrix C) when both the thermodynamics, expressed by means of a positive λ A/B spreading coefficient, and the kinetic effects, expressed by means of a dispersed phase viscosity ratio smaller than 1, acted cooperatively.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the steady-state UCM model does not describe well the sintering process of all viscoelastic materials. An effort was thus made to develop a model in which the transient rheology was taken into account. , It was concluded that the influence of viscoelasticity was limited to the first step of the coalescence process. For long times, the transient model converges to the Newtonian solution.…”
Section: Introductionmentioning
confidence: 99%
“…An effort has been made to develop a model in witch the transient rheology is taken into account [6,7]. An effort has been made to develop a model in witch the transient rheology is taken into account [6,7].…”
Section: Literature Reviewmentioning
confidence: 99%